Clitoral surgery on minors: an interview study with clinical experts of differences of sex development. Issue 6 (5th June 2019) - Liao, Lih-Mei; Hegarty, Peter; Creighton, Sarah; Lundberg, Tove; Roen, Katrina
Abstract : Objectives: Clitoral surgery on minors diagnosed with differences of sex development is increasingly positioned as a violation of human rights. This qualitative study identified how health professionals (HPs) navigate the contentious issues as they offer care to affected families. Design: Qualitative analysis of audio-recorded semistructured interviews with HPs. All of the interviews were transcribed verbatim for theoretical thematic analysis. Setting: Twelve specialist multidisciplinary care centres for children, adolescents and adults diagnosed with a genetic condition associated with differences of sex development. Participants: Thirty-two medical, surgical, psychological and nursing professionals and clinical scientists in 12 specialist centres in Britain and Sweden formed the interview sample. Results: All interviewees were aware of the controversial nature of clitoral surgery and perceived themselves and their teams as non-interventionist compared with other teams. Data analyses highlighted four strategies that the interviewees used to navigate their complex tasks: (1) engaging with new thinking, (2) holding on to historical assumptions, (3) reducing the burden of dilemmas and (4) being flexible. In response to recent reports and debates that challenge clitoral surgery on minors, HPs had revised some of their opinions. However, they struggled to reconcile their new knowledge with the incumbent norms in favour of intervention as they counsel care users with variable reactions and expectations. The flexible approach taken may reflect compromise, but the interviewees were often trapped by the contradictory values and assumptions. Conclusions: If the pathology-based vocabularies and narratives about genital diversity could be modified, and normative assumptions are questioned more often, clinicians may be more adept at integrating their new knowledge into a more coherent model of care to address the psychosocial concerns that genital surgery purports to overcome.